Effectiveness of Mask Distribution and Community Counseling in Covid-19 Prevention: A Mixed-Methods Study - Elvano Mateo; Nayaka Putri Anastasya (TRIDARMA: Pengabdian Kepada Masyarakat (PkM), 2023)
This research investigates the effectiveness of distributing masks and providing counseling to local communities in preventing the spread of Covid-19. Employing a mixed-methods approach, the study utilizes a quasi-experimental design to compare outcomes between intervention and control groups. Participants from diverse communities receive masks through distribution channels and participate in counseling sessions covering Covid-19 prevention strategies. Quantitative data, including surveys on mask usage and infection rates, are complemented by qualitative data from focus group discussions and interviews to provide a comprehensive analysis. Findings indicate a significant reduction in infection rates and improvements in mask usage and community knowledge among intervention groups. Implications for public health policy and practice are discussed, highlighting the importance of multifaceted interventions and community engagement in pandemic response efforts. Limitations of the study include the quasi-experimental design and reliance on self-reported data. Overall, the research contributes to our understanding of effective strategies for mitigating Covid-19 transmission and building resilient communities in the face of pandemics.